Role of Leptin in Mood Disorder and Neurodegenerative Disease - Zou, Xiaohan; Zhong, Lili; Zhu, Cuilin; Zhao, Haisheng; Zhao, Fangyi; Cui, Ranji; Gao, Shuohui; Li, Bingjin (Frontiers in Neuroscience, 2019)
The critical regulatory role of leptin in the neuroendocrine system has been widely reported. Significantly, leptin can improve learning and memory, affect hippocampal synaptic plasticity, exert neuroprotective efficacy and reduce the risk of several neuropsychiatric diseases. In terms of depression，leptin could modulate the levels of neurotransmitters, neurotrophic factors and reverse the dysfunction in the hypothalamic-pituitary-adrenal (HPA) axis. At the same time， leptin affects neurological diseases during the regulation of metabolic homeostasis. With regards to neurodegenerative diseases，leptin can affect neurodegenerative diseases via neuroprotection, mainly including Alzheimer's disease (AD) and Parkinson's disease （PD）. This review will summarize the mechanisms of leptin signalling within the neuroendocrine system with respect to these diseases and discuss the therapeutic potential of leptin.